Once upon a starry night : Heroes and Gods of the constellations - Mitton, Jacqueline; Balit, Christina (London : Frances Lincoln, 2005)
Presents facts about stars, nebulas, galaxies, and constellations and recounts the Greek myths that provided widely-known names for ten constellations, from Andromeda to Pegasus.
5.0
K-3.
K-3
Keywords: Astronomy -- Juvenile literature; Constellations -- Juvenile literature; Mythology -- Juvenile literature; Stars -- Juvenile literature; Astronomy; Constellations; Mythology, Greek; Stars; Astronomy; Classical mythology; Constellations; Stars